Pengaruh penggunaan CTL (Contextual Teaching and Learning) terhadap hasil belajar fisika materi pokok momentum siswa kelas XI SMA Negerei 3 Padangsidimpuan - Sartika, Evi Dewi; Sari, S.Pd., M.Pd, Lia Purnama (Jurnal Physics Education (PhysEdu), 2024)
This study aims to look at the picture of the use of CTL with the learning outcomes of the subject matter physics momentum, after that we will see a significant effect of the use of CTL and resulted in the subject matter of momentum physics class XI student of SMA Negeri 3 Padangsidimpuan. Experimental method used in this research. The study population of students of class XI SMA 3 Padangsidimpuan. Sampling was done by claster sampling technique. The number of samples in this study was a class XI IPA-3 were 30. In obtaining the data, the researchers gave the test. Data analysis is a two-step technique that will get a descriptive analysis of the results of the use of CTL 3.2 as word gori "Very Well" and the subject matter of physics learning outcomes of students 80 momentum as the category of "Good". Secondly, the alternative hypothesis t-test at the 4.55 and 1.70 compared with ttabel on. so tcount bigger than t table (4.55> 1.70). With the results of the consultation indicated that the alternative hypothesis is formed in the study received.